International Trade, Labour Turnover, and the Wage Premium: Testing the Bhagwati-Dehejia Hypothesis for Canada - Eugene Beaulieu; Vivek Dehejia; Hazrat-Omar Zakhilwal (Center for Economic Studies and ifo Institute (CESifo), 2004)
In this paper we examine the impact of international trade on the absolute and relative wages of educated and less-educated workers in Canada over 1993-96. We show that after correcting for the relative supply effect of educated to less educated workers the wage differential would have been on an upward trend. Moreover, after controlling for other relevant factors influencing real wages, trade had a statistically significantly positive impact on the wages of both educated and less educated workers. However, the impact on the educated workers was four times stronger, roughly the same as the impact of technology on relative wages. We show that the observed relationship between trade and the relative wage of educated to less-educated workers does not fit the Stolper-Samuelson theoretical explanation. The observed results are more in line with the Bhagwati-Dehejia hypothesis, which posits a link from trade to wages through volatility, labour turnover, and jobless spells.
Keywords: 330